Investigation of effectiveness of surgical treatment of chronic dacryocystitis - endonasal dacryocystorhinostomy. - V. L. Borodulya; E. M. Grechka; M. E. Stepakhina; E. A. Derbina (Medičnì Perspektivi)
Prolonged and continuous lacrimation (symptom of epiphora) causes discomfort, inclination to conjunctiva infect, reduces visual acuity and ultimately the quality of life of the patient. Despite the fact that there is a large number of various surgical interventions to restore tearing in patients with chronic dacryocystitis, the problem of lacrimation remains relevant. We have studied the operation of endonasal dacryocystorhinostomy and its long-term consequences. Surgical intervention in endonasal dacryocystorhinostomy is aimed at eliminating lacrimation by eliminating stenosis and forming a new combination of the cavity of the laryngeal canal with the nasal cavity, as well as the sanation of purulent foci of infection in the throat. There were 8 surgical interventions. Period of observation of patients in the postoperative period by ophthalmologist and ENT-doctor is from 1.5 to 2 years. The evaluation of the result was carried out in 6 months or more after the operation. A complete recovery with the recovery of the tear excretion in the nasal cavity has been achieved in all patients. The formed rhinostoma was wide, well functioning. Thus, endonasal dacryocystorhinostomy is a highly effective and should be a method of choice for inflammation of the lacrimal sac at any stage of development.